Warming and phosphorus enrichment alter the size structure and body stoichiometry of aquatic gastropods - Wang, Tao; Zhang, Peiyu; Zhang, Huan; Wang, Huan; Su, Xiyang; Zhang, Min; Xu, Jun (Frontiers in Ecology and Evolution, 2022)
Aquatic gastropods are important integral components of the macroinvertebrate community in freshwater ecosystems and play critical roles in freshwater ecosystems by contributing to biodiversity, nutrient cycling, and water quality. However, the variation of aquatic gastropods’ community structure under the combined effects of warming and nutrient enrichment remains largely unknown. To investigate this question, we performed an outdoor mesocosm experiment examining the interaction of warming (a 4.5 °C increase in mean temperature above ambient conditions) and nutrient enrichment (phosphorus addition) on the aquatic gastropods’ community and dominant population (Bellamya aeruginosa). We analyzed the changes in community dynamics (abundance and biomass), size structure, and stoichiometric traits (only B. aeruginosa). Results showed that phosphorus enrichment alone had a positive effect on the total abundance and biomass of gastropods, as well as the abundance and biomass of B. aeruginosa. Warming alone only produced a positive effect on total abundance. However, the combined effects of warming and phosphorus enrichment negatively affected the biomass and abundance of the whole gastropod community and the dominant gastropod population. The body mass of B. aeruginosa increased because of warming, whereas the body mass of the gastropod community negatively responded to warming. Phosphorus enrichment alone had no remarkable effects on body mass. The combined effects of warming and phosphorus enrichment negatively affected the whole community’s body mass but had no substantial effect on the body mass of B. aeruginosa. For body stoichiometric traits, warming or phosphorus enrichment alone produced positive effects on the nitrogen and phosphorus contents of B. aeruginosa. The combined effects caused adverse effects on the contents of the two elements. The effect of warming alone only decreased the ratio of nitrogen to phosphorus. Results suggested that the response levels in size structure between the gastropod community and the dominant population differed remarkably. Composition species shift was the main cause of the decrease in aquatic gastropods’ community size structure. The shift in species composition at the whole gastropod community level caused by warming and phosphorus enrichment may result in more complex and unpredicted consequences through cascade effects on the structure and function of freshwater ecosystems.